An initial exploration on existing practices of mosque audit in Malaysia / Kamariah Ali, Sharifah Norhafiza Syed Ibrahim and Mohd Ariff Mustafa - Ali, Kamariah; Syed Ibrahim, Sharifah Norhafiza; Mustafa, Mohd Ariff (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Nowadays, a mosque does not only function as a place for prayers but also serve as a multifunction premise for other purposes such as an education center, economic hub for Muslims, community center, one stop center for the travelers, the shelter for the needy and poor people. Due to the increasing functions of a mosque, it is important for the mosque to be governed appropriately and monitored by the Islamic authorities. A mosque audit is probably required as a check and balance mechanism to ensure a mosque is being managed within the boundaries of Islamic rules and regulations. This paper aims to explore current practices of Malaysian Islamic authorities in auditing mosques in Malacca and to discover the barriers and challenges in mosque audit. This study used a qualitative method of inquiry to gather data. A semi-structured interview was conducted with the audit personnel from the Internal Audit Department of Melaka Islamic Religious Council (MIRC).